2018
DOI: 10.1111/jcmm.13996
|View full text |Cite
|
Sign up to set email alerts
|

CD147 promotes progression of head and neck squamous cell carcinoma via NF‐kappa B signaling

Abstract: CD147/basigin (BSG) is highly upregulated in many types of cancer, our previous study has found that CD147/BSG is highly expressed in head and neck squamous cell carcinoma (HNSCC) stem cells, but its role in HNSCC and the underlying mechanism is still unknown. In this study, we investigated the role of CD147 in the progression of HNSCC. Real‐time PCR, western blot and immunohistochemistry were used to detect the expression of CD147 in total 189 HNSCC tissues in compared with normal tissues. In addition, we use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 36 publications
5
25
0
Order By: Relevance
“…Nevertheless, on the basis of these findings, we further explored the possible mechanisms underlying the effect of CD147 on the development and recurrence of OSCC, especially cervical lymph node metastasis. EMT was reported to be closely related to lymph node or distant metastasis in some malignant tumours, especially squamous cell carcinomas 6,28,29 . We found that E‐cadherin expression in the OSCC tissues was significantly lower than that in the adjacent oral mucosa.…”
Section: Discussionmentioning
confidence: 61%
“…Nevertheless, on the basis of these findings, we further explored the possible mechanisms underlying the effect of CD147 on the development and recurrence of OSCC, especially cervical lymph node metastasis. EMT was reported to be closely related to lymph node or distant metastasis in some malignant tumours, especially squamous cell carcinomas 6,28,29 . We found that E‐cadherin expression in the OSCC tissues was significantly lower than that in the adjacent oral mucosa.…”
Section: Discussionmentioning
confidence: 61%
“…We discovered that the SDGs were mainly enriched in the NF−kappaB signaling pathway and DNA repair by GO and KEGG analyses. Several studies have strongly supported the associations between NF−kappaB signaling pathway and HNC [20][21][22] . Qin Y et.al found the CCL18 (chemokine (C-C motif) ligand 18) could promote the HNSCC malignancy and its level was signi cantly associated with histological grade through regulating the NF−κB signal pathway [20] .…”
Section: Discussionmentioning
confidence: 94%
“…We discovered that the SDGs were mainly enriched in the NF − kappaB signaling pathway and DNA repair by GO and KEGG analyses. Several studies have strongly supported the associations between NF − kappaB signaling pathway and HNC [20][21][22] . Qin Y et.al found that CCL18 (chemokine (C-C motif) ligand 18) could promote the HNSCC malignancy and its level was signi cantly associated with histological grade through regulating the NF − κB signal pathway [20] .…”
Section: Discussionmentioning
confidence: 94%